Nexus between health poverty and climatic variability in Pakistan: a geospatial analysis - Khan, Sami Ullah; Sheikh, Muhammad Ramzan; Dimen, Levente; Batool, Hafsah; Abbas, Asad; Nuta, Alina Cristina (Frontiers in Environmental Science, 2023)
Studies investigating the interconnection of health poverty and climatic variability are rare in spatial perspectives. Given the importance of sustainable development goals 3, goal 10, and goal 13, we explored whether the geographic regions with diverse climate structure has a spatial association with health poverty; whether spatial disparities exist across districts of Pakistan. We implied the A-F methodology to estimate the MHP index using the PSLM survey, 2019-20. The climate variables were extracted from the online NASA website. We applied the spatial techniques of Moran's I, univariate and bivariate LISA, to address the research questions. The findings revealed that the magnitude of MHP differs across districts. Punjab was found to be the better-ff whereas Baluchistan was the highest health poverty-stricken province. The spatial results indicated positive associations of MHP and climate indicators with their values in the neighbors, whereas a negative spatial association was found between the MHP and climate indicators. Also, spatial clusters and outliers of higher MHP were significant in Baluchistan and KP provinces. Government intervention and policymaker's prioritization are needed towards health and health-related social indicators, mainly in the high poverty-stricken districts, especially in Baluchistan.